Orthopaedic implant infections: interplay of associated factors - Benazir, Shazia; Nazir, Umar; Nazir, Shaista; Shafi, Azhar; Bashir, Lenah; Angmo, Dekyong; Bhat, Asifa (International Journal of Advances in Medicine, 2019)
Background: Medical implants are devices that are placed inside or on the surface of the body for functional, cosmetic or therapeutic purposes. Orthopaedic implants are usually associated with infections which lead to devastating complications for the patients. The study was conducted to evaluate the association of various factors considered to affect orthopaedic implant infections. Methods: The 100 patients with orthopaedic implant infections were included. Various patient parameters including risk factors, intervention form and type of onset of infection were recorded. Microbiological workup was done by standard techniques along with biofilm detection. Results: Early onset of infection was prevalent in cases with open fractures. Smoking and tissue destruction were the major risk factors. Longer duration of surgery was associated with early onset and polymicrobial infections. 15.5% of the isolates were strong biofilm producers. Staphylococcus aureus was the predominant biofilm producer. More biofilm producing organisms were recovered from stainless steel implants. Conclusions: Orthopaedic device-related infections lead to extreme morbidity in patients and puts a great encumberance on hospital resources. Various factors affect the outcome of orthopaedic implants. Appropriate infection control and institution specific interventions will help in reducing the magnitude of the problem.